Role And Impact Of Cooperative Coffee Producers Margamulya In The Development Of Java Preanger Coffee Farming - Nursyamsiah, Endah Djuwendah, Tuti Karyani, Hepi Hapsari, Elly Rasmikayati, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
Cooperative coffee producers Margamulya(CPCM) is one of the cooperatives that help coffee farmers in Pangalengan to access capital and market with other parties. The research result showed that Margamulya Coffee Producers Cooperative had an important role in the development of Java Preanger coffee farming in terms of procurement of production input, facilitation of production process, product marketing, financial service, business risk minimization, and human resource development. The impact of cooperative’s activities on the success of coffee farming are: ensuring the continuous input supply with cheaper price, standardization and improvement of product quality, increasing production volume, establishing effective distribution network, providing price guarantee, reducing the risk of production failure, and increasing the income of farming.Keywords : Role, Impact, Cooperative,Coffee, Farming